Desain Logo Gula Aren Pak Sulhan Desa Melati Jaya - Nirma Nirma; Yuli Maylena (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2026)
This study aims to address the brand identity and packaging issues faced by the MSME (Micro, Small, and Medium Enterprise) of Ibu Sumiati’s Banana Chips in Melati Jaya Village, Semendawai Timur District, OKU Timur Regency. The MSME possesses a competitive advantage as its main ingredient is sourced from its own garden. However, the product currently lacks a consistent brand identity, leading to inconsistent and unappealing packaging, which hinders competitiveness and market recognition. The methodology employed is Design-Based Research with an Action Research approach, involving four main stages: Observation and needs analysis, Visual Design, Implementation and Prototyping, and Evaluation. The outcome of this activity is the creation of a cohesive brand identity and packaging design for Ibu Sumiati’s banana chips and banana sale (dried banana). The implementation of this design is expected to transform the image of Ibu Sumiati’s MSME from a traditional scale to a professional one.